Psychometric Properties of Two Self-Report Suicide Assessment and Intervention Competency Measures in a Sample of Vocational Rehabilitation Support Staff. Issue 1 (29th November 2016) - Lund, Emily M.; Schultz, Jared C.; Nadorff, Michael R.; Galbraith, Kate; Thomas, Katie B.
Abstract : We analysed the psychometric properties of two published self-report suicide assessment competency rating scales – the Suicide Competency Inventory (SCI) and the Suicide Competency Assessment Form (SCAF) – in a sample of 93 public-sector vocational rehabilitation support staff from six states in the United States. Both measures demonstrated very good to excellent internal consistency in our sample. Exploratory factor analysis with principal axis factoring indicated the SCI loads on a two-factor model in this sample, as opposed to the three-factor model proposed by the measure's authors. The SCAF loaded on a single factor, consistent with the theoretical model proposed by the original authors. The SCI and SCAF were highly correlated with each other, providing initial evidence of convergent construct validity. These results provide initial support for the use of these measures as a reliable and valid means of assessing perceived suicide assessment competency in vocational rehabilitation support staff.